Taxes, Redistribution, and the Minimum Wage: A Theoretical Analysis - Allen, Stephen P. (Quarterly Journal of Economics, 1987)
This paper considers a simple general equilibrium model that contains two types of workers with differing levels of ability and a social-welfare-maximizing government. The paper shows that social welfare can sometimes be increased by supplementing an optimal linear income tax with a minimum wage, but that social welfare can never be increased by supplementing an optimal nonlinear income tax with a minimum wage.